2020
DOI: 10.1177/0021998320949635
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fibre orientation and predicting elastic properties of discontinuous long fibre thermoplastic composites

Abstract: Elastic properties in critical areas of 3 D shells made from discontinuous long fibre (DLF) composites are difficult to determine via traditional methods, due to the heterogeneity of the material and the geometry of the part. In this paper, a method is proposed to predict the local modulus of DLF composites based on a micrograph of the polished edge of a specimen. The position and orientation of each fibre are extracted from the micrograph and used in conjunction with classical lamination theory to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The crack then follows a path at the interface between two chips (plies) that have a large difference in orientation, presumably due to high shear stresses between the adjacent chips. This was verified by measuring the orientation of the two adjacent chips with the ellipse method described by Belliveau et al 16 Fibres at 0° are defined as being parallel to the longitudinal axis of the specimen. Analysis of the chip orientation on each side of the crack found in Figure 7(a) revealed an original contact between low fibre angles of approximately 9° and high fibre angles of approximately 81°, resulting in an angular difference of 72°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crack then follows a path at the interface between two chips (plies) that have a large difference in orientation, presumably due to high shear stresses between the adjacent chips. This was verified by measuring the orientation of the two adjacent chips with the ellipse method described by Belliveau et al 16 Fibres at 0° are defined as being parallel to the longitudinal axis of the specimen. Analysis of the chip orientation on each side of the crack found in Figure 7(a) revealed an original contact between low fibre angles of approximately 9° and high fibre angles of approximately 81°, resulting in an angular difference of 72°.…”
Section: Discussionmentioning
confidence: 99%
“…These micrographs show that the DLF panels are porosity free, which validates the moulding cycle of Figure 3. The surface finish was also defect free, which reveals an advantage of PEI (amorphous) over PEEK (semicrystalline) 16 as the matrix for compression moulding applications.…”
Section: Panel Fabricationmentioning
confidence: 95%
See 1 more Smart Citation
“…3 However, recent studies have shown that when chip flow is encountered during moulding, in-plane isotropic properties can no longer be assumed. [6][7][8][9] Chip flow leads to fibre alignment in the direction of flow, creating a highly anisotropic material with lower properties perpendicular to the flow. Furthermore, using digital imaging correlation, some researchers have observed highly nonuniform strain fields caused by irregularity in fibre alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to use multiscale characterisation methodologies to better understand the materials' microstructure and macrostructure; this is the focus of this study. In the literature, a vast number of methods exist that have been explored within the field of fibre-reinforced composite materials, such as fibre orientation [30][31][32], fibre length [33,34], interfibre spacing [35], fibre diameter [36], fibre connectivity [37], fibre curvature [37], fibre volume fraction (FVF) [38], and porosity [39,40]. Each microstructural descriptor is measured using individual approaches by destructive methods, e.g., optical microscopy, including bright-field and polarised light microscopy [41,42] and mechanical testing, such as tensile testing or compression testing [11,21,27]; or non-destructive methods, e.g., X-raybased techniques, such as X-ray diffraction [43], X-ray computed tomography [35,37,[44][45][46][47] and ultrasound computed tomography [48]; ultrasonic testing [49][50][51], nuclear magnetic resonance spectroscopy and Raman spectroscopy [52,53]; image analysis using different algorithms, such as Fourier analysis [54], gradient-based methods, and structure tensor methods.…”
Section: Introductionmentioning
confidence: 99%